Synthesis of non-stationary automatic flight control system for approaching - Краснопольський, А. О. (Proceedings of National Aviation University (archive), 2002)
The method of synthesis of the structure of the automatic control system, which allows a large gain without disturbance of stability, is proposed. An adaptive system is considered in the form of an algorithm and a structural scheme that can be used in a program of onboard computing complex on an example of a civil aircraft, for automatic adjustment of the gain, based on the requirements of the specified stability of the transition process